Analysis of Teacher Readiness in the Implementation of Competency Assessment Minimum (AKM) Independent Class at SDN 44 Mandau - Zefira Salsabilla; Guslinda; Antosa, Zariul (Education Generation Journal, 2024)
This study aims to find out how the readiness of teachers in implementing AKM classes independently. This type of research is qualitative research. Sources of data in this study are teachers and proctors. The results showed that the teacher's readiness to carry out AKM classes independently at SDN 44 Mandau as a whole was declared not ready, this was because of the inhibiting factors there was a lack of understanding of the teacher in using technology and there were no infrastructure facilities that could be used as a learning system, as well as for to the students the teacher does not give extra hours and only does it in the usual learning hours. However, this problem can be resolved because of the self and mental readiness that has been prepared by the teacher so that the implementation can run effectively